Perlindungan Hukum Terhadap Konsumen Rokok Elektrik - wiwin mochtar wiyono; suryati suryati; Nurlaeli Sukesti Ariani Nasution (Faculty of Law, Universitas Wijayakusuma, 2021)
Abstract The circulation of goods and/or services in society at this time also affects the development of cigarette products, both kretek cigarettes, white cigarettes, cigars and even the development of electric cigarettes. The government has issued many regulations related to smoking. One of the most popular cigarettes in society is the electric cigarette which aims to protect consumers from harm. However, e-cigarettes also contain dangers that many consumers are not aware of. The form of protection for cigarette consumers has been issued PP No. 109 of 2012 concerning the Safety of Materials Containing Addictive Substances in the Form of Tobacco Products for Health. The PP also applies to e-cigarettes. This study uses a normative juridical method, with secondary data as the main data in the form of legislation, and related literature. The data were analyzed qualitatively. In general, in consumer protection law there are several principles of responsibility, namely the principle of responsibility based on the element of error/negligence, the principle of the presumption of being responsible (presumption of liability), the principle of the presumption of not always being responsible (presumption of nonliability) and the principle of absolute responsibility (strict liability). The responsibility of business actors to consumers using e-cigarettes is included in the principle of presumption of liability, known as a reverse proof system where business actors as defendants are always considered responsible for all losses suffered by consumers until they can prove that the business actor not guilty. Abstrak Peredaran barang dan/jasa di masyarakat pada saat sekarang juga mempengaruhi perkembangan produk rokok baik rokok kretek, rokok putih, cerutu dan bahkan berkembang adanya rokok elektrik. Pemerintah telah mengeluarkan banyak peraturan yang berkaitan dengan rokok. Salah satu rokok yang sedang banyak digemari masyarakat adalah rokok elektrik yg bertujuan melindungi konsumen agar terhindar dari bahaya. Namun rokok elektrik pun juga mengandung bahaya yang tidak disadari oleh bnyak konsumen. Bentuk perlindungan bagi konsumen rokok telah dikeluarkan PP No. 109 Tahun 2012 tentang Pengamanan Bahan Yang Menandung Zat Adiktif Berupa Produk Tembakau Bagi Kesehatan. PP tersebut juga berlaku untuk rokok elektrik. Penelitian ini menggunakan metode yuridis normatif, dengan data sekunder sebagai data utama yang berupa peraturan perundang-undangan, dan literatur yang terkait. Data dianalisa secara kualitatif. Pada umunya dalam hukum perlindungan konsumen terdapat beberapa prinsip-prinsip tanggung jawab, yaitu prinsip tanggung jawab berdasarkan unsur kesalahan/kelalaian, prinsip praduga untuk selalu bertanggung jawab (presumption of liability), prinsip praduga untuk tidak slalu bertanggung jawab (presumption of nonliability) dan prinsip tanggung jawab mutlak (strict liability). Tanggung jawab pelaku usaha terhadap konsumen penggunaan rokok elektrik termasuk ke dalam prinsip praduga untuk selalu bertanggung jawab (presumption of liability) yang dikenal dengan sistem pembuktian terbalik dimana pelaku usaha selaku tergugat selalu dianggap bertanggung jawab atas segala kerugian yang dialami konsumen sampai dapat membuktikan bahwa pelaku usaha tidak bersalah.